Sulfhydration-associated phosphodiesterase 5A dimerization mediates vasorelaxant effect of hydrogen sulfide - Sun, Yan (Oncotarget, 2017)
The study was designed to examine if the vasorelaxant effect of hydrogen sulfide was mediated by sulfhydration-associated phosphodiesterase (PDE) 5A dimerization. The thoracic aorta of rat was separated and the vasorelaxant effects were examined with in vitro vascular perfusion experiments. The dimerization and sulfhydration of PDE 5A and soluble guanylatecyclase (sGC) were measured. PDE 5A and protein kinase G (PKG) activities were tested. Intracellular cGMP content was detected by enzyme-linked immunosorbent assay (ELISA). The results showed that NaHS relaxed isolated rat vessel rings at an EC50 of (1.79 ± 0.31)×10(−5)mol/L, associated with significantly increased PKG activity and cGMP content in vascular tissues. Sulfhydration of sGC β1 was increased, while the levels of sGC αβ1 dimers were apparently decreased after incubation with NaHS in vascular tissues. Moreover, PDE 5A homodimers were markedly decreased, and accordingly the PDE 5A activity demonstrated by the content of 5′-GMP was significantly decreased after incubation with NaHS or GYY4137. Mechanistically, both NaHS and GYY4137 significantly enhanced the PDE 5A sulfhydration in vascular tissues. DTT partially abolished the effects of NaHS on PDE 5A activity, cGMP content and vasorelaxation. Therefore, the present study for the first time suggested that H(2)S exerted vasorelaxant effect probably via sulfhydration-associated PDE 5A dimerization.